Pendampingan Mitra Usaha Kelompok Wanita Tani (KWT) Kecamatan Punggur Kabupaten Lampung Tengah - Ari Gusnita; Yuditya Wardhana; Syeni Rakhmadani (Fakultas Ilmu Sosial dan ilmu Politik, 2022)
Women Farmers Group (KWT) is a group consisting of women or housewives who have a job farming or planting rice. KWT has a noble goal, namely to help the family's economy so that they can prosper economically. The problem with KWT in general is that there are obstacles in terms of product marketing. As happened in Punggur sub-district, Central Lampung Regency, the absence of maximum assistance has become a problem for the people who are members of the KWT. The purpose of this service with the theme of Business Partner Assistance is to help the community, especially KWT Punggr, to be independent and able to make sales in various places of cooperation or partnership so that they can achieve prosperity. The method in this service is to provide assistance to the KWT community. The result of this service is the existence of collaborations formed to partner with KWT. While the conclusion in this service is that it can be said to be running. Because until mid-July 2022 they are still working together/partners.